MEKANISME PENYELESAIAN SENGKETA TUMPAHAN MINYAK DI LAUT BERDASARKAN HUKUM INTERNASIONAL - Satrio Parikesit Kusumo Nugroho; Anto Ismu Budianto (Reformasi Hukum Trisakti, 2022)
There have been numerous leaks caused by oil spills in Indonesian territorial seas, but the Montara oil refinery leak and spill in the Timor Sea, which has been happening since 2009, is particularly significant and is currently being appealed. The way the issue is phrased what procedure is in place to settle claims involving international oil spills? Statements made about the oil spill in the Indonesian Timor Sea by the governments of Australia and Indonesia. According to the agreement, the study methodology is normative research on efforts to settle disputes about marine pollution. As of this writing, data processing is qualitative, and conclusions are drawn using deductive reasoning. The study's findings, analysis, and conclusion were used in the court case between Daniel Aristabulus Sanda and PTTEP Australasia (Ashmore Cartier) Pty Ltd, NSD Number 1245 of 2016, which Judge Yates J decided on March 19, 2021, at the Australian Federal Court in the State of New South Wales. It is ideal for Indonesia and Australia to come to a bilateral agreement that governs the way in which states are held accountable for marine contamination brought on by oil spills from offshore oil drilling operations.